Phosphorus legacy advances the negative response of surface soil organic carbon to altered precipitation regimes - Qiao Liu; Fangchao Wang; Fu-Sheng Chen; Junjie Huang; Shengnan Wang; Jianjun Li; Xiangjiang Liu; Zeqing Ma; Huiming Wang; Xiaofei Hu; Yiqi Luo (Soil Biology and Biochemistry, 2026)

LsS6K acts as a negative regulator of thiamethoxam tolerance in Laodelphax striatellus - Shu Fang; Yuyang Shi; Mi Zhou; Huijun Zhang; Hong Fu; Qun Zheng; Kun Qian; Jianjun Wang (Pesticide Biochemistry and Physiology, 2026)

Insights from the genomic epidemiology of Vibrio parahaemolyticus in Nantong, China: A comparative genomics study of the classic ST3 and emerging ST2516 lineages - Ailong Huang; Yue Zhao; Shicheng Fu; Ende Zhong; Xiaolong Ding; Weibing Zhang; Jianjun Dai; Xiangkai Zhuge (Food Microbiology, 2026)

Rhizosphere microbial α diversity dominates network complexity in governing soil multifunctionality during alpine grassland restoration - Fayi Li; Yubin Liu; Hu Yan; Zongcheng Cai; Shouquan Fu; Shancun Bao; Hairong Zhang; Jianjun Shi (Plant and Soil, 2026)

A KED-based framework for enhanced subcanopy topography retrieval leveraging TanDEM-X InSAR and spaceborne LiDAR data - Tao Zhang; Jianjun Zhu; Zhiwei Liu; Haiqiang Fu; Changcheng Wang; Zenghui Fan; Yumin Fang; Yang Liu (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Thermally driven self-assembly of triterpenoid-fructan supramolecular particles contributes significantly to the efficacy of Zexie Tang against MASH - Senjie Chen; Yongbin Xu; Dewen Liu; Lijuan Xie; Chenyang Zhou; Bolin Wu; Lingyan Zhu; Guosheng Fu; Siqi Gao; Wei Liu; Caihua Sun; Luping Qin; et al. (Carbohydrate Polymers, 2026)

Organ‐Wide qPCR Profiling Reveals High Trypanosome Intensity in Oral Mucosa of Cultured Larimichthys crocea - Zhang QingWei; Wang Yanjie; Xie Jianjun; Yan Xiaojun; Tao Zhen; Fu Peipei (Journal of Fish Diseases, 2026)
Trypanosomiasis has emerged as a significant health concern in cultured large yellow croaker ( Larimichthys crocea ), yet the organ‐level distribution of the causative trypanosome within this host remains poorly characterized. The trypanosome was confirmed as Trypanosoma sp. Lc by 18S rRNA gene sequencing (99.9% identity to two isolates from L. crocea in Fujian); its precise taxonomic placement remains under discussion. We quantified trypanosome distribution across 12 organ types of naturally microscopy‐confirmed infected L. crocea ( n = 6; collected from Zhujiajian Island, Zhoushan, China) by RT‐qPCR targeting the trypanosome 18S rRNA gene, with conspecific fish confirmed uninfected by blood smear microscopy ( n = 3) included as biological negative controls. Trypanosome 18S rRNA signal was detected in all 12 organ types from infected L. crocea but not in any biological negative controls. Among organ types, the oral mucosa exhibited the highest trypanosome mean intensity (554.1 copies/μg RNA) significantly higher than that of mesentery (0.5 copies/μg RNA), muscle (0.8 copies/μg RNA) and gonad (1.5 copies/μg RNA) ( p Trypanosoma sp. Lc in large yellow croaker and define key ultrastructural characteristics that complement molecular identification. The high trypanosome 18S rRNA mean intensity observed in oral mucosa and heart may help inform sample collecting for molecular detection and field surveillance in large yellow croaker aquaculture.

Extending Zipf's law: hierarchical scaling analysis and the dynamics of city-level CO2 emissions in China - Sen Liang; Ke Wang; Qiu Jin; Jianjun Zhang; Zhenlin Fan; Iskid Jacquet; Bangning Fu (Sustainable Cities and Society, 2026)

Global lactylation is downregulated despite lactate accumulation: lactylome data and functional insights during ISKNV infection - Zhourui Sun; Yinjie Niu; Xiaozhe Fu; Qiang Lin; Xianglin Cao; Hongru Liang; Xia Luo; Baofu Ma; Wenwen Xiao; Ningqiu Li; Jianjun Chen (Fish & Shellfish Immunology, 2026)

A PolSAR rotation model for crop classification and soil moisture retrieval in complex agricultural environments - Wentao Han; Mingxu Wang; Dengshan Huang; Qinghua Xie; Haiqiang Fu; Cui Zhou; Jianjun Zhu (International Journal of Remote Sensing, 2026)

Exogenous microbial inoculation drives alpine compost maturity by overcoming thermodynamic barriers and reshaping fungal networks - Zongcheng Cai; Fayi Li; Hu Yan; Shancun Bao; Hairong Zhang; Shouquan Fu; Ran Qin; Enqi Yang; Quanfang Lei; Jianjun Shi (Journal of Environmental Chemical Engineering, 2026)

Synergistic Application of Composite Microbial Inoculants and Forage-Specific Fertilizer Enhances Herbage Yield, Quality, and Oil Ecological Functions of Sown Grasslands in Alpine Mining Areas - Zongcheng Cai; Fayi Li; Shouquan Fu; Shancun Bao; Hairong Zhang; Ran Qin; Quanfang Lei; Enqi Yang; Jianjun Shi (Journal of Soil Science and Plant Nutrition, 2026)

Orbital Climate–Wildfire coupling-driven vegetation succession in the early permian North China Basin - Di Chen; Di Gao; Jianjun Hou; JunJiao Yang; XueBo Fu; Chi Cui; Bianqing Guo (Journal of Asian Earth Sciences, 2026)

Bridging accelerated cell-level degradation to module-relevant failure mechanisms in TOPCon solar cells and modules - Xinyuan Wu; Wei Wu; Weiguang Yang; Yan Zhang; Jiexi Fu; Xutao Wang; Jing Yuan; Jianjun Nie; Zhencong Qiao; Chao An; Feng Li; Lin Lv; et al. (Chemical Engineering Journal, 2026)

Synergistic interactions between EM inoculants and organic fertilizers promote ecosystem recovery by restructuring fungal communities in alpine permafrost mining areas - Zongcheng Cai; Jianjun Shi; Liangyu Lv; Pei Gao; Shouquan Fu; Yu Liu; Qingqing Liu; Fayi Li; Hairong Zhang; Shancun Bao (Journal of Soils and Sediments, 2026)

Precise ligand defect nanoarchitectonics in integrity-preserving 2D Zn-TCPP for efficient photocatalytic H2 evolution - Xingyan Liu; Jianjun Pu; Haibo Zhou; Hongwen Zhang; Yafeng Qian; Min Fu; Yuyu Fang; Youzhou He; Siping Wei (Journal of Environmental Chemical Engineering, 2026)

Genome-wide methylation and transcriptome analysis in koi carp (Cyprinus carpio var. koi): Uncovering novel molecular mechanisms in skin color differentiation and pigmentation - Xiulan Shi; Xiaoyu Chen; Wenbin Zhu; Jun Guo; Kai Lin; Jianjun Fu; Lanmei Wang; Mingkun Luo; Zaijie Dong (Aquaculture, 2026)

Carbon dots with concurrent antibacterial, anti-inflammatory, and osteogenic activities for visualized therapy of infected bone defects through modulating bone immune microenvironment - Yan Xia; Jinyan Hu; Jianjun Qiu; Panfeng Wang; Lei Li; Shuogui Xu; Bijiang Geng; Shuming Pan; Qingge Fu (Chemical Engineering Journal, 2026)

Sub-canopy topography estimation based on sub-aperture decomposition and least-squares collocation from LuTan-1 InSAR data - Huacan Hu; Haiqiang Fu; JianJun Zhu; Yanzhou Xie; Qijin Han; Aichun Wang; Mingxia Zhang; Jun Hu (Journal of Geodesy, 2026)
LuTan-1 (LT-1) provides unprecedented L-band bistatic interferometric synthetic aperture radar (InSAR) data for terrain mapping. In forested areas, although the L-band exhibits strong penetration capability, the phase center is still located above the bare ground due to forest volume scattering. Furthermore, the bistatic acquisition provides only single-baseline, single-polarization data, leading to an underdetermined issue for existing scattering models in sub-canopy topography inversion. To address these issues, this study proposes a sub-canopy topography estimation framework based on sub-aperture decomposition and the least-squares collocation (LSC) method. The contributions of this study are: 1) assessing the feasibility of sub-aperture decomposition under LT-1’s small azimuth observation angles; 2) using sub-aperture coherence to provide additional observations and address the underdetermination issue of InSAR inversion; and 3) developing an LSC-based method to separate and calibrate LT-1 orbital and scattering model errors, with the latter arising from complex terrain, forest property variations, and model solution. The proposed framework was tested and validated using LT-1 InSAR data acquired over coniferous, evergreen broadleaf, and tropical forests. The estimated sub-canopy topography achieved a root mean square error (RMSE) between 1.22 and 3.85 m, representing an average improvement of over 60% compared to the InSAR DEM and an improvement of over 30% compared to the initial terrain that did not account for scattering model errors. Moreover, the results indicate that the proposed method also exhibits superior performance under varying terrain and forest conditions, further demonstrating its effectiveness and robustness.

An ICESat-2 photon cloud classification model coupling slope and complex canopy structure in forest areas - Yi Li; Haiqiang Fu; Jianjun Zhu (Remote Sensing of Environment, 2025)

Experimental and mechanistic study of copper leaching from copper converter slag enhanced by glycine - Jianjun Sun; Yanxiong Fu; Han Wang; Tianfu Zhang; Peilun Shen; Dianwen Liu (Journal of Environmental Chemical Engineering, 2025)

High-resolution subcanopy topography inversion for boreal forest areas based on an IWCM-aided multi-baseline InSAR method - Huiqiang Wang; Zhimin Feng; Haiqiang Fu; Jianjun Zhu; Ruiping Li; Zhiwei Liu; Lei Wang; Shuai Hao; Qiuliang Zhang; Lei Zhao; Zheng Zhao (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Responses of δ13C and δ15N in Carex parvula to Ecological Restoration and the Coupling Mechanism with Soil Versatility in Alpine Regions - Fayi Li; Pingna Yin; Liangyu Lv; Shancun Bao; Zongcheng Cai; Shouquan Fu; Jianjun Shi (Ecological Engineering, 2025)

Regulation of pine wood pretreatment and pyrolysis by hydrogen bond donors in choline chloride deep eutectic solvents - Shuheng Zhao; Shang Wang; Zhuojie Li; Qiaolong Zhai; Junhao Hu; Kui Wang; Fei Fu; Jianjun Hu (Chemical Engineering Journal, 2025)

Does the cropping system have a substantial influence on greenhouse gas emissions? Dynamics and key factors-based insights from an empirical study of China - Jiongxin Chen; Jianjun Zhang; Shu Fu; Sen Liang; Ke Wang (Agricultural and Forest Meteorology, 2025)

Crop height retrieval from polarimetric SAR data using machine learning: A comparative and validation study - Shuaifeng Hu; Qinghua Xie; Xing Peng; Qi Dou; Jinfei Wang; Juan M. Lopez-Sanchez; Jiali Shang; Haiqiang Fu; Jianjun Zhu; Wenming Zhou (Computers and Electronics in Agriculture, 2025)

Resilience-oriented road network recovery strategies with urban air mobility under rainstorm-induced waterlogging - Luyao Wang; Jianjun Wu; Xin Yang; Hao Fu; Shuang Yang; Ting Wang (Journal of Transport Geography, 2025)

Environmental variables affect the effectiveness of ecosystem services of ecological restoration project: Evidence from Xiangjiang River Basin-Dongting Lake - Shu Fu; Jianjun Zhang; Yufei Li; Wei Chen; Yaping Zhang; Kexin Yi; Yixin Dai (Journal of Cleaner Production, 2025)

Integrating and mapping spatial heterogeneity of the ecosystem: a novel approach to indicating environmental threats - Xiaojie Wei; Yanan Zhang; Jianjun Zhang; Ke Wang; Sen Liang; Shu Fu (Environmental Research, 2025)

Highly selective reduction of CO2 to CH4 mediated by 2D/0D Cs3Bi2Br9/BiOBr heterojunctions with atomic-level intimate interfaces - Tingting Ren; Yanqing Zhang; Suning Fu; Yuanming Hou; Jiaxin Wang; Jingyi Qin; Zhengzheng Xie; Jianjun Yang; Zhongjie Guan; Shilong Jiao; Qiuye Li; Xianwei Fu (Chemical Engineering Journal, 2025)

Effectiveness of governmental and policy initiatives in reducing agricultural greenhouse gas emissions: An empirical analysis of West Africa - Iskid Jacquet; Jianjun Zhang; Ke Wang; Sen Liang; Shu Fu; Shidong Liu (Environmental Development, 2025)

Insight into the piezo-activation of peroxymonosulfate by 1T/2H-MoS2: piezopotential boosting the formation of Mo-peroxymonosulfate complexes as the major reactive species - Tian Jiang; Chang Cai; Honggen Peng; Jianjun Li; Xiaoxiao Fu; Chunyang Nie; Zhimin Ao (Chemical Engineering Journal, 2025)

Path analysis of trace elements and physiological and biochemical indices associated to mild cognitive impairment in elderly Chinese - Peiyi Liu; Haiyan Huang; Qimei Zhou; Ying Zhi; Jiahui Wang; Ying Fu; Erwei Gao; Xiaohu Ren; Xiao Chen; Xinfeng Huang; Jianjun Liu; Xifei Yang (Environmental Pollution, 2025)

A new approach to color correction and equalization for generating mars global color image mosaics from Tianwen-1 MoRIC images - Xin Ren; Xiaoxia Zhang; Wangli Chen; Wei Yan; Xingguo Zeng; Xu Tan; Xingye Gao; Qiang Fu; Lin Guo; Qing Zhang; Zhaopeng Chen; Guobin Yu; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Knockout of the fih gene by CRISPR/Cas9 enhances the hypoxia tolerance in grass carp (Ctenopharyngodon idella) - Huimei Zhang; Ziquan Yang; Jianjun Fu; Ziming Yuan; Jie Chen; Rengao Shen; Guodong Zheng; Shuming Zou; Zaijie Dong (Aquaculture, 2025)

Response of ecological condition in ecologically fragile areas to disturbance from extreme precipitation event: An empirical analysis from the loess plateau - Kexin Yi; Jianjun Zhang; Haoyi Lei; Wei Chen; Yaping Zhang; Shu Fu; Ke Wang (Journal of Cleaner Production, 2025)

Evaluation of muscle quality and movement-related traits in two common carp strains under a rice–fish farming system - Yating Gong; Mingkun Luo; Xianbo Zhang; Ning Qin; Wenbin Zhu; Lanmei Wang; Jianjun Fu; Zaijie Dong (Aquaculture International, 2025)

Effects of temperature on growth performance, gonad development, immunity, and antioxidant response of hybrid red tilapia (Oreochromis niloticus ♂ × Oreochromis aureus ♀) - Endalh Mekonnen; Yujie Deng; Yude Sun; Lanmei Wang; Jianjun Fu; Mingkun Luo; Zaijie Dong; Wenbin Zhu (Aquaculture International, 2025)

Study on seeding delay time and lag distance of automatic section control system for maize seeder - Lin Ling; Hanqing Li; Yuejin Xiao; Weiqiang Fu; Jianjun Dong; Liwei Li; Rui Liu; Xinguang Huang; Guangwei Wu; Zhijun Meng; Bingxin Yan (Computers and Electronics in Agriculture, 2025)

MeshAC: A 3D mesh generation and adaptation package for multiscale coupling methods - Kejie Fu; Mingjie Liao; Yangshuai Wang; Jianjun Chen; Lei Zhang (Computer Physics Communications, 2025)

Improving resilience to extreme heat events through green space morphology: A threshold-based perspective - Yixin Dai; Jianjun Zhang; Shu Fu; Wei Chen; Yaping Zhang; Kexin Yi (Sustainable Cities and Society, 2025)

Combined skin injury model from airblast overpressure and seawater immersion in rats: establishment, characterization, and mechanistic insights - Jinpeng Du; Zhao Li; Yi Kong; Wei Song; Zhongming Chen; Mengde Zhang; Yuyan Huang; Chao Zhang; Xu Guo; Linhao Hou; Yaxin Tan; Liting Liang; et al. (Journal of Molecular Histology, 2025)

How landscape characteristics impact land surface temperature in the context of urban spatial heterogeneity: A case study from Beijing, China - Wei Chen; Jianjun Zhang; Chenyan Huang; Shu Fu (Urban Climate, 2025)

Measuring heat transfer index (HTI): A new method to quantify the spatial influence of land surface temperature between adjacent urban spaces - Wei Chen; Jianjun Zhang; Chenyan Huang; Shu Fu; Sen Liang; Ke Wang (Sustainable Cities and Society, 2025)

Identification of novel natural anti-browning agents based on phenotypic and metabolites differences in potato cultivars - Yueming Tang; Yiwen Yang; Fangyao Luo; Jinghong Luo; Jianjun Hu; Haoqiang Yu; Wanchen Li; Jia Gao; Fengling Fu (Food Chemistry, 2025)

A general three-component polarimetric SAR interferometry target decomposition - Shuaifeng Hu; Qinghua Xie; J. David Ballester-Berman; Qi Dou; Xing Peng; Youjun Wang; Haiqiang Fu; Jianjun Zhu (Advances in Space Research, 2024)

The role of mitochondrial dysfunction in the association between trace metals and QTc prolongation in the aged population - Jiahui Wang; Peiyi Liu; Yankui Lin; Xia Zhang; Lingling Lin; Fengqi Wu; Ying Fu; Desheng Wu; Xiaohu Ren; Haiyan Huang; Xifei Yang; Jianjun Liu (Science of The Total Environment, 2024)

Soil moisture retrieval over agricultural fields with machine learning: A comparison of quad-, compact-, and dual-polarimetric time-series SAR data - Changchang Lv; Qinghua Xie; Xing Peng; Qi Dou; Jinfei Wang; Juan M. Lopez-Sanchez; Jiali Shang; Lei Chen; Haiqiang Fu; Jianjun Zhu; Yang Song (Journal of Hydrology, 2024)

Improved forest height mapping using multibaseline low-frequency PolInSAR data based on effective selection of dual-baseline combinations - Yanzhou Xie; Haiqiang Fu; Jianjun Zhu; Changcheng Wang; Qinghua Xie; Jie Wan; Wentao Han (Remote Sensing of Environment, 2024)

Heating pattern and effects of built-up land in response to influencing factors: A statistical estimation of 172 Chinese cities - Wei Chen; Jianjun Zhang; Yaping Zhang; Shu Fu; Kexin Yi; Yixin Dai (Journal of Cleaner Production, 2024)

Genome-wide association study reveals candidate genes critical for skin pigmentation in common carp (Cyprinus carpio) strains including koi - Xiulan Shi; Wenbin Zhu; Jun Guo; Kai Lin; Jianjun Fu; Lanmei Wang; Yalun Dong; Mingkun Luo; Zaijie Dong (Aquaculture, 2024)

Selective benzene hydroalkylation: Ni/Ni PS/HY catalysts for enhanced cyclohexylbenzene formation - Wenhan Chen; Sen Zhao; Ley Boon Sim; Jianjun Li; Xianghua Liu; Jile Fu; Nuowei Zhang; Jinbao Zheng; Binghui Chen (Fuel, 2024)

Insights into microbial metabolic coordination under driving force of different conductive materials-mediated direct interspecies electron transfer during anaerobic digestion - Xinwei Zhou; Mengxia Guo; Xiangzhuang Fu; Dexin Wang; Jianjun Liao; Wen Xu; Hongjun Han (Chemical Engineering Journal, 2024)

New dawn of ginsenosides: regulating gut microbiota to treat metabolic syndrome - Xue Bai; Rongzhan Fu; Jianjun Deng; Haixia Yang; Chenhui Zhu; Daidi Fan (Phytochemistry Reviews, 2024)

Molecular characterization and function of hif1a and fih1 in response to acute thermal stress in American shad (Alosa sapidissima) - Zhengyuan Liang; Songqin Hu; Yalun Dong; Linghong Miao; Wenbin Zhu; Bingbing Feng; Jianjun Fu; Mingkun Luo; Lanmei Wang; Zaije Dong (Fish Physiology and Biochemistry, 2024)

A 76-m per pixel global color image dataset and map of Mars by Tianwen-1 - Jianjun Liu; Xin Ren; Wei Yan; Wangli Chen; Xingguo Zeng; Xiaoxia Zhang; Xu Tan; Xingye Gao; Qiang Fu; Dingxin Liu; Lin Guo; Qing Zhang; et al. (Science Bulletin, 2024)

Risk of heavy metal(loid) compositions in fine particulate matter on acute cardiovascular mortality: a poisson analysis in Anyang, China - Chaofan Shi; Jianjun Zhi; Hongsheng Zhao; Wan Wang; Hongjin Zhang; Guoyu Zhou; Xiaoli Fu; Yue Ba (International Journal of Biometeorology, 2024)

Risk performance analysis approach for convoy operations via a hybrid model of STPA and DBN: A case from ice-covered waters - Xiaoming Zhu; Shenping Hu; Zhuang Li; Jianjun Wu; Xue Yang; Shanshan Fu; Bing Han (Ocean Engineering, 2024)

Preliminary analysis of the catastrophic February 22nd 2023 Xinjing open-pit mine landslide, Inner Mongolia, China - Zhigang Li; Weile Li; Qiang Xu; Huiyan Lu; Hao Fu; Pengyu Guo; Jianjun Zhao; Congwei Yu (Landslides, 2024)

Microwave co-pyrolysis of industrial sludge and waste biomass: Product valorization and synergistic mechanisms - Yang Liu; Asif Ali Siyal; Chunbao Zhou; Chenglong Liu; Jie Fu; Yingwen Zhang; Bang Yao; Li Chao; Huimin Yun; Jianjun Dai; Xiaotao Bi (Chemical Engineering Journal, 2024)

High-temperature stress response: Insights into the molecular regulation of American shad (Alosa sapidissima) using a multi-omics approach - Mingkun Luo; Wenbin Zhu; Zhengyuan Liang; Bingbing Feng; Xudong Xie; Yulin Li; Ying Liu; Xiulan Shi; Jianjun Fu; Linghong Miao; Zaijie Dong (Science of The Total Environment, 2024)

Influence of speed measurement method on performance of an electric-drive maize precision planter - Lin Ling; Guangwei Wu; Changkai Wen; Yuejin Xiao; Weiqiang Fu; Jianjun Dong; Jianhong Ding; Zhijun Meng; Bingxin Yan (Biosystems Engineering, 2024)

Comparative microwave catalytic pyrolysis of cellulose and lignin in nitrogen and carbon dioxide atmospheres - Yang Liu; Chunbao Zhou; Asif Ali Siyal; Chenglong Liu; Yingwen Zhang; Jie Fu; Huimin Yun; Jianjun Dai; Xiaotao Bi (Journal of Cleaner Production, 2024)

Catalytic degradation of crystal violet and methyl orange in heterogeneous Fenton-like processes - Long Wang; Chunbao Zhou; Yanxin Yuan; Yajie Jin; Yang Liu; Zhihui Jiang; Xiangtong Li; Jianjun Dai; Yingwen Zhang; Asif Ali Siyal; Wenya Ao; Jie Fu; et al. (Chemosphere, 2023)

High-resolution sub-canopy topography mapping via TanDEM-X DEM combined with future P-band BIOMASS PolInSAR data - Jianjun Zhu; Zhiwei Liu; Haiqiang Fu; Cui Zhou; Yi Zhou; Huiqiang Wang; Yanzhou Xie (Journal of Geodesy, 2023)

Mitigating greenhouse gas emissions from agriculture in Benin: spatial estimation and reduction options - Iskid Jacquet; Jianjun Zhang; Ke Wang; Sen Liang; Shu Fu; Shidong Liu (Environment, Development and Sustainability, 2023)

A review on polyphenols and their potential application to reduce food allergenicity - Xiaowen Pi; Yuxue Sun; Jianjun Cheng; Guiming Fu; Mingruo Guo (Critical Reviews in Food Science and Nutrition, 2023)

Effect of mulberry leaf polysaccharides on the physicochemical, rheological, microstructure properties and in vitro starch digestibility of wheat starch during the freeze-thaw cycles - Yang Fu; Jianjun Zhou; Dezheng Liu; Juan Manuel Castagnini; Francisco J. Barba; Yue Yan; Xiaorong Liu; Xuedong Wang (Food Hydrocolloids, 2023)

Digital terrain, surface, and canopy height model generation with dual-baseline low-frequency InSAR over forest areas - Jianjun Zhu; Yanzhou Xie; Haiqiang Fu; Changcheng Wang; Huiqiang Wang; Zhiwei Liu; Qinghua Xie (Journal of Geodesy, 2023)

Deep spatiotemporal transcriptome analysis provides new insights into early development of koi carp (Cyprinus carpio var. koi) - Mingkun Luo; Xiulan Shi; Jun Guo; Kai Lin; Wenbin Zhu; Jianjun Fu; Lanmei Wang; Zaijie Dong (Aquaculture, 2023)

Urinary essential and toxic metal mixtures, and type 2 diabetes mellitus: Telomere shortening as an intermediary factor? - Duo Zhang; Xiao Chen; Ke Huang; Quanzhi Zheng; Ying Fu; Jiaojiao Ma; Xiaohu Ren; Benhong Xu; Peiyi Liu; Jianjun Liu; Shaoyou Lu (Journal of Hazardous Materials, 2023)

The youngest lunar zircon reveals an extremely fractionated nature of Chang’e-5 basalt - Qin Zhou; Yu Liu; Saihong Yang; Qiu-Li Li; Yi Chen; Guangliang Zhang; Hongbo Zhang; Bin Liu; Dawei Liu; Jianjun Liu; Fu-Yuan Wu; Xian-Hua Li; et al. (Geochimica et Cosmochimica Acta, 2023)

Optimizing soil and fertilizer management strategy to facilitate sustainable development of wheat production in a semi-arid area: A 12-year in-situ study on the Loess Plateau - Peng Wu; Gang Zhao; Hua Huang; Qi Wu; Kemoh Bangura; Tie Cai; Min Sun; Jianfu Xue; Jianjun Zhang; Yi Dang; Shuying Wang; Gang Zhou; et al. (Field Crops Research, 2023)

Urban agglomeration waterlogging hazard exposure assessment based on an integrated Naive Bayes classifier and complex network analysis - Mo Wang; Xiaoping Fu; Dongqing Zhang; Siwei Lou; Jianjun Li; Furong Chen; Shan Li; Soon Keat Tan (Natural Hazards, 2023)

Co-exposure to parabens and triclosan and associations with cognitive impairment in an elderly population from Shenzhen, China - Xiaohu Ren; Yilan Deng; Wei Liu; Jinfeng Fu; Zhihong Huang; Duo Zhang; Qinru Xiao; Xiangyu Li; Xiao Chen; Xinfeng Huang; Jianjun Liu; Shaoyou Lu (Chemosphere, 2023)

Integrative analysis uncovers the mechanism underlying the environmental adaptation of an indigenous crucian carp (Carassius auratus gibelio) in Dong's Rice Fish Duck System - Mingkun Luo; Xianbo Zhang; Wenbin Zhu; Qianwen Min; Jinli Hu; Jianjun Fu; Xiulan Shi; Bingjie Jiang; Yating Gong; Lanmei Wang; Ting Liu; Zaijie Dong (Aquaculture, 2023)

Investigation on effect of anti-cavitation edge on performance and leakage vortex characteristics of tubular turbine for ocean power generation - Chenhao Li; Xingqi Luo; Guangkuan Wu; Yongyuan Fu; Jianjun Feng; Guojun Zhu (Ocean Engineering, 2023)

A polarimetric projection-based scattering characteristics extraction tool and its application to PolSAR image classification - Wentao Han; Haiqiang Fu; Jianjun Zhu; Shurong Zhang; Qinghua Xie; Jun Hu (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Design, synthesis and biological evaluation of aminopyrimidine derivatives bearing dihydroquinoxalinone as novel EGFRL858R/T790M kinase inhibitors against non-small-cell lung cancer - Liping Fu; Yu Cao; Jingbai Chen; Ruoyu He; Yanmei Zhao; Yaping Zhao; Jianjun Xi; Rangxiao Zhuang; Chongmei Tian (Medicinal Chemistry Research, 2023)

Screening and Identification of Interacting Proteins of Mitfa in Red Tilapia - Bingjie Jiang; Lanmei Wang; Jianjun Fu; Wenbin Zhu; Mingkun Luo; Zaijie Dong (Fishes, 2023)
Skin color variation and differentiation are bottlenecks in the aquaculture industry of red tilapia. The mitfa gene primarily regulates melanocyte survival and proliferation in fish skin pigmentation. In this study, a recombinant expression vector for Mitfa expression was successfully constructed. After induction and purification, nearly 600 μg of Mitfa protein was purified from the fermentation supernatant. His pull-down assay, followed by LC-MS/MS analysis, revealed 10 proteins that interact with the Mitfa protein. Five of these proteins were annotated in the melanogenesis and tyrosine metabolism pathways, including Krt, Tpm, Myh, Tyr and Dct. The purified Mitfa recombinant protein was injected into red tilapia, and its activity and function were examined. The expression levels of the mitfa, tyr, tyrp1, and dct genes increased greatly in the dorsal skin after injection (p

Plow layer management during the fallow season can enhance the wheat productivity and resource utilization in a semi-arid region - Gang Zhao; Peng Wu; Fu Liu; Shangzhong Li; Jianjun Zhang; Yi Dang; Lei Wang; Shuying Wang; Wanli Cheng; Tie Cai; Tinglu Fan (Soil and Tillage Research, 2023)

The spatial configuration of buildings: A vital consideration impossible to ignore in regulating urban land surface temperature? Evidence from 35 Chinese cities - Wei Chen; Jianjun Zhang; Shidong Liu; Sen Liang; Yaping Zhang; Shu Fu (Science of The Total Environment, 2023)

Cover crop by irrigation and fertilization improves soil health and maize yield: Establishing a soil health index - Peng Li; Huijuan Zhang; Jianjun Deng; Libo Fu; Hua Chen; Chunkai Li; Li Xu; Jiaguo Jiao; Shixiang Zhang; Jidong Wang; Duo Ying; Huixin Li; et al. (Applied Soil Ecology, 2023)

Catalytic hydrolysis of corncob for production of furfural and cellulose-rich solids: Product characterization and analysis - Bang Yao; Qinhao Kang; Jie Fu; Yang Liu; Wenya Ao; Long Wang; Zhihui Jiang; Tianhao Zhang; Yongmeng Song; Zeyu Deng; Asif Ali Siyal; Jianjun Dai (Biomass and Bioenergy, 2023)

Notch1 down-regulation in lineage-restricted niches is involved in the development of mouse eccrine sweat glands - Yuzhen Wang; Bin Yao; Xianlan Duan; Jianjun Li; Wei Song; Enhejirigala; Zhao Li; Xingyu Yuan; Yi Kong; Yijie Zhang; Xiaobing Fu; Sha Huang (Journal of Molecular Histology, 2022)

Recent advances in alleviating food allergenicity through fermentation - Xiaowen Pi; Yili Yang; Yuxue Sun; Qiang Cui; Yin Wan; Guiming Fu; Hongbing Chen; Jianjun Cheng (Critical Reviews in Food Science and Nutrition, 2022)

Food irradiation: a promising technology to produce hypoallergenic food with high quality - Xiaowen Pi; Yili Yang; Yuxue Sun; Xibo Wang; Yin Wan; Guiming Fu; Xin Li; Jianjun Cheng (Critical Reviews in Food Science and Nutrition, 2022)

Ginsenoside Rb3 attenuates skin flap ischemia-reperfusion damage by inhibiting STING-IRF3 signaling - Yuanbin Li; Haifen Liu; Zhaohui Zeng; Hui Lin; Xin Chen; Xianglian Yuan; Jizhe Qiu; Fengchun Fu; Zhuang Chen; Jianjun Kuang (Journal of Molecular Histology, 2022)

Correction to: Transcriptome analysis of skin color variation during and after overwintering of Malaysian red tilapia - Bingjie Jiang; Lanmei Wang; Mingkun Luo; Jianjun Fu; Wenbin Zhu; Wei Liu; Zaijie Dong (Fish Physiology and Biochemistry, 2022)

Transcriptome analysis of skin color variation during and after overwintering of Malaysian red tilapia - Bingjie Jiang; Lanmei Wang; Mingkun Luo; Jianjun Fu; Wenbin Zhu; Wei Liu; Zaijie Dong (Fish Physiology and Biochemistry, 2022)

Identification and characterization of 76 SNP markers in the large-scale loach (Paramisgurnus dabryanus) by using SLAF sequencing - Jianjun Fu; Shunpeng Wan; Wenbin Zhu; Lanmei Wang; Mingkun Luo; Xianhu Zheng; Zaijie Dong (Conservation Genetics Resources, 2022)

Circular RNA circ-PLCD1 functions as a tumor suppressor in non-small cell lung cancer by inactivation of PI3K/AKT signaling pathway - Jiming Si; Jianjun Jin; Jingjing Sai; Xiaoting Liu; Xiao Luo; Zhenqiang Fu; Jing Wang (Human Cell, 2022)

Refining the conversion between phase and height in airborne and UAV-borne SAR interferometry - Huiqiang Wang; Jianjun Zhu; Haiqiang Fu; Yanan Yu (International Journal of Remote Sensing, 2021)

Impacts of land use change on ecosystem service value in Lijiang River Basin, China - Ning Li; Jinye Wang; Haoyu Wang; Bolin Fu; Jianjun Chen; Wen He (Environmental Science and Pollution Research, 2021)

Metagenomic insights into soil microbial communities involved in carbon cycling along an elevation climosequences - Zhongmin Dai; Huadong Zang; Jie Chen; Yingyi Fu; Xuehua Wang; Huaiting Liu; Congcong Shen; Jianjun Wang; Yakov Kuzyakov; Joscha N. Becker; Andreas Hemp; Albert Barberán; et al. (Environmental Microbiology, 2021)
Summary Diversity and community composition of soil microorganisms along the elevation climosequences have been widely studied, while the microbial metabolic potential, particularly in regard to carbon (C) cycling, remains unclear. Here, a metagenomic analysis of C related genes along five elevations ranging from 767 to 4190 m at Mount Kilimanjaro was analysed to evaluate the microbial organic C transformation capacities in various ecosystems. The highest gene abundances for decomposition of moderate mineralizable compounds, i.e. carbohydrate esters, chitin and pectin were found at the mid‐elevations with hump‐shaped pattern, where the genes for decompositions of recalcitrant C (i.e. lignin) and easily mineralizable C (i.e. starch) showed the opposite trend (i.e. U‐shaped pattern), due to high soil pH and seasonality in both low and high elevations. Notably, the gene abundances for the decompositions of starch, carbohydrate esters, chitin and lignin had positive relationships with corresponding C compounds, indicating the consistent responses of microbial functional profiles and metabolites to elevation climosequences. Understanding of adaptation of microbial communities, potential function and metabolites to elevation climosequences and their influencing factors provided a new insight for the regulation of terrestrial C storage.

Estimation of subcanopy topography based on single-baseline TanDEM-X InSAR data - Huiqiang Wang; Haiqiang Fu; Jianjun Zhu; Zhiwei Liu; Bing Zhang; Changcheng Wang; Zhiwei Li; Jun Hu; Yanan Yu (Journal of Geodesy, 2021)

Development of SNP markers for the bighead carp (Hypophthalmichthys nobilis) by using transcriptomic sequences - Rui An; Jianjun Fu; Bingjie Jiang; Wenbin Zhu; Lanmei Wang; Mingkun Luo; Zaijie Dong (Conservation Genetics Resources, 2020)

Front Cover - Jianjun Wang; Pierre Legendre; Janne Soininen; Chih‐Fu Yeh; Emily Graham; James Stegen; Emilio O. Casamayor; Jizhong Zhou; Ji Shen; Feiyan Pan (Global Ecology and Biogeography, 2020)

Temperature drives local contributions to beta diversity in mountain streams: Stochastic and deterministic processes - Jianjun Wang; Pierre Legendre; Janne Soininen; Chih‐Fu Yeh; Emily Graham; James Stegen; Emilio O. Casamayor; Jizhong Zhou; Ji Shen; Feiyan Pan (Global Ecology and Biogeography, 2020)
Aim Community variation (i.e. beta diversity) along geographical gradients is of substantial interest in ecology and biodiversity reserves in the face of global changes. However, the generality in beta diversity patterns and underlying processes remains less studied across trophic levels and geographical regions. We documented beta diversity patterns and underlying ecological processes of stream bacteria, diatoms and macroinvertebrates along six elevational gradients. Locations Asia and Europe. Methods We examined stream communities using molecular and morphological methods. We characterised community uniqueness with local contributions to beta diversity (LCBD), and investigated the drivers of its geographic patterns using Mid‐Domain Effect (MDE), coenocline simulation, Raup‐Crick null model approach, and through comparisons to environmental factors. MDE is a stochastic model by considering species elevational range, while coenocline simulation is a deterministic model by considering species niche optima and tolerance. The null model provides possible underlying mechanisms of community assembly with the degree to which deterministic processes create communities deviating from those of null expectations. Results Across all taxa, we revealed a general U‐shaped LCBD‐elevation relationship, suggesting higher uniqueness of community composition at both elevational ends. This pattern was confirmed and could be explained by both stochastic and deterministic models, that is, MDE and coenocline simulation, respectively, and was supported by the dominance of species replacement. Temperature was the main environmental factor underlying elevational patterns in LCBD. The generalists with broad niche breadths were key in maintaining community uniqueness, and the higher relative importance of deterministic processes resulted in stronger U‐shaped patterns regardless of taxonomic group. Conclusions Our synthesis across both mountains and taxonomic groups clearly shows that there are consistent elevational patterns in LCBD among taxonomic groups, and that these patterns are explained by similar ecological mechanisms, producing a more complete picture for understanding and bridging the spatial variation in biodiversity under changing climate.

Discovery of 3-(thiophen/thiazole-2-ylthio)pyridine derivatives as multitarget anticancer agents - Jiankang Zhang; Jianjun Xi; Ruoyu He; Rangxiao Zhuang; Limin Kong; Liping Fu; Yanmei Zhao; Chong Zhang; Linghui Zeng; Jingyi Lu; Rujia Tao; Zhengmengtong Liu; et al. (Medicinal Chemistry Research, 2019)

Performance Simulation of the Transportation Process Risk of Bauxite Carriers Based on the Markov Chain and Cloud Model - Jianjun Wu; Shenping Hu; Yongxing Jin; Jiangang Fei; Shanshan Fu (Journal of Marine Science and Engineering, 2019)
China imports a large quantity of bauxite each year. Bauxite in fine particles with high moisture has a high risk of liquefaction during the maritime transportation process, which is harmful to the stability and safety of the carrier. To ensure safe shipping, it is necessary to pay attention to the effects of the operation of cargo, the ship’s maneuvering and the ocean environment during the whole transportation process. The simulation of the process risk helps to develop measures to intervene with the cargo behavior to keep the risk to an acceptable level. This study examined the transportation process of a bauxite carrier using the Markov Chain method at different stages of loading, unberthing, departure and sea navigation. Based on the risk transfer matrix of the operational status at different stages of transportation, a cloud simulation model was developed to analyze the transportation process risk of a ship carrying bulk bauxite. Results: the research revealed that the risk evolution rule of the solid bulk cargoes with potential liquefaction during the transportation process, especially bauxite. The risk alteration during the prophase of the transportation process conforms to the rule of the “spoon curve”. Conclusions: a simulation model of the process risk based on the Markov Chain Cloud is suitable for the simulation analysis of the transportation risk of the bulk bauxite carrier. The outcomes of this study may contribute to better safety management to prevent the occurrence of ship capsizing.

Microsatellite records for volume 11, issue 1 - Da-Qing Chen; Zaijie Dong; Min Fang; Jianjun Fu; Xiang-Yang Jia; Bingjie Jiang; Jingmiao Li; Qingqing Li; Suhui Liao; Ping Liu; Yulin Liu; Guocheng Shu; et al. (Conservation Genetics Resources, 2019)

Elevational patterns and hierarchical determinants of biodiversity across microbial taxonomic scales - Chih‐Fu Yeh; Janne Soininen; Anette Teittinen; Jianjun Wang (Molecular Ecology, 2019)
Microbial biogeography is gaining increasing attention due to recent molecular methodological advance. However, the diversity patterns and their environmental determinants across taxonomic scales are still poorly studied. By sampling along an extensive elevational gradient in subarctic ponds of Finland and Norway, we examined the diversity patterns of aquatic bacteria and fungi from whole community to individual taxa across taxonomic coverage and taxonomic resolutions. We further quantified cross‐phylum congruence in multiple biodiversity metrics and evaluated the relative importance of climate, catchment and local pond variables as the hierarchical drivers of biodiversity across taxonomic scales. Bacterial community showed significantly decreasing elevational patterns in species richness and evenness, and U‐shaped patterns in local contribution to beta diversity (LCBD). Conversely, no significant species richness and evenness patterns were found for fungal community. Elevational patterns in species richness and LCBD, but not in evenness, were congruent across bacterial phyla. When narrowing down the taxonomic scope towards higher resolutions, bacterial diversity showed weaker and more complex elevational patterns. Taxonomic downscaling also indicated a notable change in the relative importance of biodiversity determinants with stronger local environmental filtering, but decreased importance of climatic variables. This suggested that niche conservatism of temperature preference was phylogenetically deeper than that of water chemistry variables. Our results provide novel perspectives for microbial biogeography and highlight the importance of taxonomic scale dependency and hierarchical drivers when modelling biodiversity and species distribution responses to future climatic scenarios.

Underlying topography extraction over forest areas from multi-baseline PolInSAR data - Haiqiang Fu; Jianjun Zhu; Changcheng Wang; Zhiwei Li (Journal of Geodesy, 2018)

CASCIRE surveillance network and work on avian influenza viruses - Yuhai Bi; Weifeng Shi; Jianjun Chen; Quanjiao Chen; Zhenghai Ma; Gary Wong; Wenxia Tian; Renfu Yin; Guanghua Fu; Yongchun Yang; William J. Liu; Chuansong Quan; et al. (Science China Life Sciences, 2017)

Genetic parameter estimates and genotype by environment interaction analyses for early growth traits in grass carp (Ctenopharyngodon idella) - Jianjun Fu; Yubang Shen; Xiaoyan Xu; Chengchu Liu; Jiale Li (Aquaculture International, 2015)

Inversion of vegetation height from PolInSAR using complex least squares adjustment method - HaiQiang Fu; ChangCheng Wang; JianJun Zhu; QingHua Xie; Rong Zhao (Science China Earth Sciences, 2015)

Identification, characterization and feeding response of peptide YYb (PYYb) gene in grass carp (Ctenopharyngodon idellus) - Yong Chen; Narayan Prasad Pandit; Jianjun Fu; Da Li; Jiale Li (Fish Physiology and Biochemistry, 2014)

An overview of US state drought plans: crisis or risk management? - Xinyu Fu; Mark Svoboda; Zhenghong Tang; Zhijun Dai; Jianjun Wu (Natural Hazards, 2013)

Multiplex microsatellite PCR sets for parentage assignment of grass carp (Ctenopharyngodon idella) - Jianjun Fu; Yubang Shen; Xiaoyan Xu; Yong Chen; Da Li; Jiale Li (Aquaculture International, 2013)

Comparison of Effects of Vanadium Absorbed by Coprinus comatus with Those of Inorganic Vanadium on Bone in Streptozotocin-Diabetic Rats - Guangbin Wang; Ming He; Pei Yi; Jiashi Wang; Bin Li; Jianjun Li; Yonghui Fu; Lunhao Bai; Qin Fu (Biological Trace Element Research, 2012)

Isolation and characterization of novel microsatellite markers in Water monitor (Varanus salvator) - Meilan Fu; Dongmei Yu; Jianjun Peng; Ying Wang; Saifei Gao; Lili Wang; Xiqing Liu; Shijia Hu; Lingfu Gao (Conservation Genetics Resources, 2011)

Development of 15 dinucleotide microsatellite markers from the enriched library of yellow-breasted Bunting (Emberiza aureola) - Dongmei Yu; Jianjun Peng; Saifei Gao; Meilan Fu; Lili Wang; Shijia Hu; Xiqing Liu; Huijian Hu (Conservation Genetics Resources, 2011)

Isolation and characterization of novel microsatellite markers in Gekko gecko (Reptilia: Gekkonidae) - Saifei Gao; Dongmei Yu; Jianjun Peng; Ying Wang; Meilan Fu; Xiqing Liu; Shijia Hu; Lili Wang; Lingfu Gao (Conservation Genetics Resources, 2011)

Land Use-Based Landscape Planning and Restoration in Mine Closure Areas - Jianjun Zhang; Meichen Fu; Ferri P. Hassani; Hui Zeng; Yuhuan Geng; Zhongke Bai (Environmental Management, 2011)

Analysis of genetic variation and bottleneck in a captive population of Siamese crocodile using novel microsatellite loci - Dongmei Yu; Jianjun Peng; Shijia Hu; Saifei Gao; Meilan Fu; Huijian Hu; Jiejian Zou (Conservation Genetics Resources, 2011)

Significant association of SNP rs2106261 in the ZFHX3 gene with atrial fibrillation in a Chinese Han GeneID population - Cong Li; Fan Wang; Yanzong Yang; Fenfen Fu; Chengqi Xu; Lisong Shi; Sisi Li; Yunlong Xia; Gang Wu; Xiang Cheng; Hui Liu; Chuchu Wang; et al. (Human Genetics, 2011)

New microsatellite resources in Chinese big-headed turtle (Platysternon megacephalum) - Jianjun Peng; Dongmei Yu; Shijia Hu; Lili Wang; Cuina Xin; Yushu Zhang; Saifei Gao; Meilan Fu; Huijian Hu (Conservation Genetics Resources, 2010)

Effects of plant types on physico-chemical properties of reclaimed mining soil in Inner Mongolia, China - Yao Fu; Changcun Lin; Jianjun Ma; Tingcheng Zhu (Chinese Geographical Science, 2010)

3D AVO analysis for identifying thin continental sandstone interbeds and deep volcanic rocks - lei Fu; Jianmin Wang; Fenglin Cui; Jianjun Xu; Xiangjun Zhang; Xiangbo Kong (Applied Geophysics, 2005)